2022
DOI: 10.1186/s43166-022-00129-x
|View full text |Cite|
|
Sign up to set email alerts
|

Consensus evidence-based clinical practice recommendations for the management of fibromyalgia

Abstract: Background Because of the subjective character of symptoms, absence of a diagnostic test, modest response to treatments, and, at times, patient reports of important functional disability, fibromyalgia remains a challenge for the treating health care professionals in the standard clinical practice. The aim of this study was to develop an up-to-date consensus and evidence-based clinical practice guidelines for a treat-to-target management of fibromyalgia. Fifteen key clinical questions were ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Similarly, a study from China reported that rheumatologists recognized some of the FM-related symptoms but had limited knowledge on the diagnostic criteria. Eighty percent of the respondents declared they had difficulties in treating FM patients (12) It has been evident that the subjective character of symptoms, absence of a diagnostic test, modest response to treatments remain as challenges for the treating health care professionals in the standard clinical practice (9). As well, the presence of several somatic complaints confounds the condition, and the diagnosis of FM is frequently overlooked (21).…”
Section: Discussion:-mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a study from China reported that rheumatologists recognized some of the FM-related symptoms but had limited knowledge on the diagnostic criteria. Eighty percent of the respondents declared they had difficulties in treating FM patients (12) It has been evident that the subjective character of symptoms, absence of a diagnostic test, modest response to treatments remain as challenges for the treating health care professionals in the standard clinical practice (9). As well, the presence of several somatic complaints confounds the condition, and the diagnosis of FM is frequently overlooked (21).…”
Section: Discussion:-mentioning
confidence: 99%
“…Management of FM includes both pharmacologic and non-pharmacological interventions. Drug therapy is not mandatory, and health education, aerobic exercise, and cognitive-behavioral therapy are considered the main lines of treatment (8,9).…”
Section: Introduction:-mentioning
confidence: 99%